Dynamics of the Subducted Izanagi-Pacific Plates Since the Mesozoic and Its Implications for the Formation of Big Mantle Wedge Beneath Eastern Asia - Wu, Bingcheng; Wang, Yongming; Huang, Jinshui (Frontiers in Earth Science, 2022)
The slab dynamics of the subducted Izanagi-Pacific plate is still a subject of controversy and its relationship with the tectonic evolution of Eastern Asia remains not well explored. Here, we perform 3-D global convection models to investigate the slab dynamics of the Izanagi-Pacific plate beneath Eastern Asia since the Mesozoic time. We introduce a tracking technique in numerical models to explicitly distinguish the Izanagi slab and the Pacific slab during their subduction processes. We find that all subducted Izanagi slabs have completely fallen into the lower mantle until the late Cenozoic and the stagnant slabs currently observed at the mantle transition zone depth beneath Eastern Asia are entirely from the Pacific plate. We also find that multiple slab stagnation events have occurred during the subduction of the Izanagi plate in the Mesozoic time (~150-120 Ma, 90-70 Ma) with a timescale of tens of million years. The stagnation of the subducted slabs facilitates the formation of a big mantle wedge beneath the overriding lithosphere and the time periods of the mantle wedge are consistent with the episodes of magmatic activities in Eastern Asia.